The Effect Of Market Segmentation And Product Distribution On Product Sales Volume PT. Garuda Mas Perkasa Medan - Pasaribu, Defi Amelia; Nasution, Muhammad Amri; Firah, Al (Universitas Dharmawangsa Medan, 2024)
This research aims to determine and analyze the effect of market segmentation and product distribution on sales volume at PT Garuda Mas Perkasa Medan. The type of research in this study is quantitative with an associative approach. The population of this study were employees of PT Garuda Mas Perkasa Medan. The sample selection method uses saturated sampling, the number of samples used is 50 sample data. Before conducting research, first test the instrument with validity test and reliability test. Prerequisite test analysis includes normality test, multicollinearity test and heteroscedasticity test. The data analysis method uses multiple linear regression. The results of this study are in accordance with the first hypothesis, that market segmentation affects sales volume. This can be seen from the test results which show that the value of 3.915 is greater than 2.010 with a significance value of 0.000 less than 0.05. The results of this study are in accordance with the second hypothesis, that product distribution has an effect on sales volume. This can be seen from the test results which show that the value of 3.580 is greater than 2.010 with a significance value of 0.000 smaller than 0.05. The results of the study are in accordance with the third hypothesis, that market segmentation and product distribution simultaneously affect sales volume. This can be seen from the F test which shows a significance value smaller than 0.05, which is 0.000. Then Fcount> Ftable (26.845> 3.190).